Synthesis of lanthanide oxysulfides activated by Eu3+. A topochemical reaction - Luiz, J. M. [UNESP]; Stucchi, E. B. [UNESP]; Barelli, N. [UNESP] (Wiley, 1996)
The oxysulfide compounds La2O2S:Eu and Y2O2S were obtained directly from thermodecomposition of the respective oxalate compounds under argon and sulfur vapor, the obtained compounds were analyzed by infrared spectroscopy, X ray diffraction and luminescence spectroscopy. The particle size distribution and crystalline habit of the compounds were observed by scanning electron microscopy. Although the particle size of the oxysulfide was found to be 30%-40% smaller than the precursor oxalates, the initial morphology was completely maintained, which indicates the occurrence of a topochemical reaction from oxalates to oxysulfides. © Gauthier-Villars.